Improving Students’ Writing Skills Through Integrated Methods (Open Academia: Journal of Scholarly Research, 2025)
This study investigates the effectiveness of integrated methods for improving students' writing skills in secondary education. By combining various instructional strategies, including collaborative writing, technology integration, and genre-based approaches, the research aims to determine their impact on students' writing proficiency. A mixed-methods approach was employed, incorporating quantitative assessments and qualitative feedback from students and teachers. The findings indicate that integrated methods significantly enhance writing skills, leading to increased student engagement and motivation